Enhancing Worldwide Supply Chain Effectiveness: An Integrated Decision-Making Method for Choosing Strategic Third-Party Logistics (3PL) Sites - Mrunal Hemantbhai Panwala (CV. Multi Kreasi Media, 2022)
This paper presents a comprehensivse study on the strategic selection of Third-Party Logistics (3PL) locations, leveraging a multicriteria decision-making (MCDM) framework. As global supply chains become increasingly complex, the choice of 3PL providers and their locations has a significant impact on operational efficiency and service quality. Through an extensive literature review, this research identifies the key criteria influencing 3PL location selection, including cost, infrastructure quality, geopolitical stability, and market accessibility. Employing a case study approach, the paper applies an Analytic Hierarchy Process (AHP) to evaluate and prioritize these factors, providing a quantifiable decision-making tool for businesses. The findings offer a nuanced understanding of the trade-offs involved in 3PL location decisions, and the paper concludes with actionable recommendations for supply chain managers and directions for future research.